Free vitamin D3 index and vitamin D‐binding protein in multiple sclerosis: A presymptomatic case–control study. (4th June 2022) - Grut, Viktor; Biström, Martin; Salzer, Jonatan; Stridh, Pernilla; Lindam, Anna; Alonso‐Magdalena, Lucia; Andersen, Oluf; Jons, Daniel; Gunnarsson, Martin; Vrethem, Magnus; Hultdin, Johan; Sundström, Peter
Abstract: Background and purpose: High levels of 25‐hydroxyvitamin D3 (25[OH]D3 ) are associated with a lower risk for multiple sclerosis (MS). The bioavailability of 25(OH)D3 is regulated by its main plasma carrier, vitamin D‐binding protein (DBP). Free 25(OH)D3 can be estimated by also measuring DBP concentration. In addition, DBP has immunomodulatory functions that may independently affect MS pathogenesis. No previous studies have assessed free 25(OH)D3 or DBP in presymptomatically collected samples. This study was undertaken to assess free 25(OH)D3 and DBP as risk factors for MS. Methods: A nested case–control study was performed with presymptomatic serum samples identified through cross‐linkage of MS registries and Swedish biobanks. Concentration of 25(OH)D3 was measured with liquid chromatography and DBP levels with sandwich immunoassay. Free 25(OH)D3 was approximated as free vitamin D3 index: (25[OH]D3 /DBP) × 10 3 . MS risk was analyzed by conditional logistic regression, calculating odds ratios (ORs) with 95% confidence intervals (CIs). Results: Serum samples from 660 pairs of matched cases and controls were included. At <20 years of age, high levels of free vitamin D3 index were associated with a lower risk of MS (highest vs. lowest quintile: OR = 0.37, 95% CI = 0.15–0.91, p for trend across quintiles = 0.04). At age 30–39 years, high levels of DBP were associated with a lower MS risk (highest vs. lowest quintile: OR = 0.36, 95% CI = 0.15–0.85, p for trend = 0.02). Conclusions: These findings support the hypothesis that high levels of free 25(OH)D3 at a young age reduce the risk of MS later in life. They also implicate a role for DBP in MS etiology. Abstract : The association of free vitamin D3 index, vitamin D‐binding protein, and the risk of developing multiple sclerosis was assessed in a case–control study of presymptomatically collected samples. High free vitamin D3 index before the age of 20 years was associated with a lower risk of developing multiple sclerosis later in life. High levels of vitamin D binding protein after the age of 30 years were associated with a lower risk of developing multiple sclerosis.